The Dynamics of Competition and Employee Satisfaction in Influencing Company Performance with Sustainable Innovation as an Intervening Variable at PT Solusi Bangun Indonesia - Deswan Prambudi Priandono (Journal AGENCY, 2025)
The increasingly dynamic business competition demands companies to continuously improve performance to maintain market competitiveness. employee satisfaction and sustainable innovation are key factors in addressing these challenges, especially in the cement industry, which is characterized by intense competition and the need for sustainability. PT Solusi Bangun Indonesia faces significant pressure to adapt to market changes while maintaining optimal performance. However, there remains a research gap regarding how business competition dynamics and customer satisfaction directly and indirectly influence company performance through sustainable innovation. This study aims to analyze the impact of business competition dynamics and employee satisfaction on company performance, with sustainable innovation as an intervening variable. A quantitative approach was employed in this research, with data collected through surveys of Manager within PT Solusi Bangun Indonesia. Data analysis was conducted using Structural Equation Modeling (SEM) to identify relationships between variables.